PARTAI POLITIK LOKAL DALAM TATA HUKUM INDONESIA - Ansari, Muhammad Insa (TANJUNGPURA LAW JOURNAL, 2017)
In the Indonesian legal system, local political parties introduced and allowed in Aceh province along with the enactment of Law No. 11 Year 2006 on Governing Aceh (UUPA). UUPA has set a lot of things related to local political parties, including the definition, formation, principles, objectives, and functions, rights and obligations, prohibitions, membership and sovereignty of members, financial sanctions, to the supervision of local political parties. Development of local political parties in Aceh province represents a new chapter in the development of democracy in Indonesia. Implementation of the UUPA associated with local political parties, the government has issued Government Regulation No. 20 Year 2007 on Local Political Parties in Aceh. In line with the Government of Aceh has prepared regulations related to local political parties, among them the Aceh Qanun No. 8 of 2007 on Financial Aid to Political Party and Local Political Parties and Aceh Qanun No. 3 of 2008 on political parties and the setting of local political parties in the regulation of central government and local government regulations indicate the existence of local political parties in the Indonesian legal system.